The Relationship Between Safety Climate and Safety Commitment: A Case Study in Alps Electric (Malaysia) Sdn Bhd. - Sordani, Yom (2011)
This study was carried out to investigate current practices in safety aspects with emphasize on relationship between safety climate and safety commitment perception among employees in a multinational electronic manufacturing company of ALPS Electric (Malaysia) Sdn. Bhd. This study will examine the relationship between safety climate and safety commitment to safety in order to achieve performance in safety and workers associated with the perception of safety has been practiced in the ALPS. Safety is an important issue at this time, but most employees or employers do not feel it as an important process in the success of long-term safety. Understanding of the concept of safety among employees will help employers to better understand the safety needs of ALPS and any legal requirements that must be followed. Findings from this study found that factors influencing the success of the safety system at work place is a safety climate and commitment to safety in reducing accidents with involving from employers and employees. In this study, using SPSS version 19 to measured the results of studies and tests of hypotheses perceived safety climate and safety commitment to achieve the safety performance in organization. The study found that there was a distinct relationship between the ages, gender and employment status. While no significant relationship between job tenure and experience involved in the accident. The existence of a positive relationship between safety climate and commitment practiced in the ALPS in this study.